The Impact Of Economic Sanctions Applied To The Foreign Trade Sector In Syria 2000-2018 - رضوان حسام (Latakia University Journal - Economic and Legal Sciences Series, 2021)
It is a discussion of the issue of international economic sanctions and the motives for imposing them on the Syrian Arab Republic, clarifying the impact of these sanctions on the foreign trade sector and the mechanism for dealing with them, The study adopted the descriptive and analytical approach. The researcher conducts a descriptive study of economic sanctions, and foreign trade in general, and then an analysis of the indicators of Syrian foreign trade in order to demonstrate the impact of the economic sanctions imposed on Syria on these indicators before and after the crisis. As for the sources of all data, they were the Central Bureau of Statistics and the Syrian Export Development and Promotion Authority. It adopted econometric statistical methods, such as time-series stability tests and regression analysis using the least squares method, and the most important results were as follows: There is a statistically significant impact of economic sanctions on Syrian exports during the period. There is a statistically significant impact of economic sanctions on Syrian imports during the period. There is no statistically significant effect of the economic sanctions on the Syrian temporary entry. There is a statistically significant impact of the economic sanctions on Syrian transit during the period.